2018
DOI: 10.1038/s41598-018-34683-2
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and photoluminescent properties of Tb3+ doped carbon nanodots

Abstract: Carbon nanodots (CNDs) doped with Tb ions were synthesized using different synthetic routes: hydrothermal treatment of a solution containing carbon source (sodium dextran sulfate) and TbCl3; mixing of CNDs and TbCl3 solutions; freezing-induced loading of Tb and carbon-containing source into pores of CaCO3 microparticles followed by hydrothermal treatment. Binding of Tb ions to CNDs (Tb-CND coupling) was confirmed using size-exclusion chromatography and manifested itself through a decrease of the Tb photolumine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that in comparison with the traditional methods, such as sorption from solution and coprecipitation, the FIL technique provides more efficient and controlled sorption of active substances and nanoparticles on the surface of porous micron and submicron particles. The FIL method finds application in obtaining composite particles, drug delivery systems, , carbon nanodots (CNDs), fluorescent microcapsules, , optoacoustic contrast agents, contrast agents for MRI, photocatalytic particles, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in comparison with the traditional methods, such as sorption from solution and coprecipitation, the FIL technique provides more efficient and controlled sorption of active substances and nanoparticles on the surface of porous micron and submicron particles. The FIL method finds application in obtaining composite particles, drug delivery systems, , carbon nanodots (CNDs), fluorescent microcapsules, , optoacoustic contrast agents, contrast agents for MRI, photocatalytic particles, etc.…”
Section: Introductionmentioning
confidence: 99%